2008
DOI: 10.1017/s1041610207006655
|View full text |Cite
|
Sign up to set email alerts
|

Physical, social and productive leisure activities, cognitive decline and interaction with APOE-ε4 genotype in Chinese older adults

Abstract: Increased leisure activity, especially productive activities more than physical or social activities, was associated with a lowered risk of cognitive decline. APOE-epsilon 4 genotype individuals appeared to be more vulnerable to the effects of low and high levels of leisure activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
146
3
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(166 citation statements)
references
References 28 publications
11
146
3
6
Order By: Relevance
“…More recently, some of these risk gene variants have been associated with cognitive decline, more concretely with poor memory performance in population-based studies (Barral et al 2012;Pedraza et al 2013). Parallel with these studies, there is accruing evidence about the benefits in cognition of lifestyle-related habits such as physical and cognitive and social activities (Hamer and Chida 2009; Kareholt et al 2011;Morgan et al 2012;Niti et al 2008;Sattler et al 2012) and nutrition in terms of nutrients and foods with conflicting results (Coley et al 2008). Regarding dietary patterns as a whole, a protective effect of MedDiet on cognitive function (Kesse-Guyot et al 2013), cognitive decline (Tsivgoulis et al 2013;Tangney et al 2011;Feart et al 2009;Scarmeas et al 2006) and development of mild cognitive impairment (Scarmeas et al 2009b;Roberts et al 2010) and dementia (Roberts et al 2010;Gu et al 2010;Scarmeas et al 2006Scarmeas et al , 2009a has been found in several observational studies but not in other cohort studies (Psaltopoulou et al 2008; Samieri et al Table 4 Multivariable-adjusted means and differences (95 % CI) for the association between each of the SNPs and cognitive assessment (Clock Drawing Test) according to intervention status Overall CLU (rs11136000) CLU ( (Martinez-Lapiscina et al 2013a, b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, some of these risk gene variants have been associated with cognitive decline, more concretely with poor memory performance in population-based studies (Barral et al 2012;Pedraza et al 2013). Parallel with these studies, there is accruing evidence about the benefits in cognition of lifestyle-related habits such as physical and cognitive and social activities (Hamer and Chida 2009; Kareholt et al 2011;Morgan et al 2012;Niti et al 2008;Sattler et al 2012) and nutrition in terms of nutrients and foods with conflicting results (Coley et al 2008). Regarding dietary patterns as a whole, a protective effect of MedDiet on cognitive function (Kesse-Guyot et al 2013), cognitive decline (Tsivgoulis et al 2013;Tangney et al 2011;Feart et al 2009;Scarmeas et al 2006) and development of mild cognitive impairment (Scarmeas et al 2009b;Roberts et al 2010) and dementia (Roberts et al 2010;Gu et al 2010;Scarmeas et al 2006Scarmeas et al , 2009a has been found in several observational studies but not in other cohort studies (Psaltopoulou et al 2008; Samieri et al Table 4 Multivariable-adjusted means and differences (95 % CI) for the association between each of the SNPs and cognitive assessment (Clock Drawing Test) according to intervention status Overall CLU (rs11136000) CLU ( (Martinez-Lapiscina et al 2013a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, genome-wide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) at the CLU, CR1 and PICALM loci that increase the risk of late-onset AD (Harold et al 2009;Lambert et al 2009). A higher educational level and higher engagement in physical, cognitive and social activities are lifestyle factors that may reduce the risk of dementia or cognitive decline (Hamer and Chida 2009;Kareholt et al 2011;Morgan et al 2012;Niti et al 2008;Sattler et al 2012). Nutritional epidemiology has examined the potential benefit on cognition of fatty acids (van Gelder et al 2007), vitamins (Mangialasche et al 2010;Tangney et al 2009), fish (van Gelder et al 2007), fruit and vegetables (Hughes et al 2010) with favorable but not fully consistent results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 15 prospective studies [5,[8][9][10][11][12][13][14][15][16][17][18] were included in the analysis. Of these, three conducted analyses separately for men and women and so were entered into the final analysis each as a single paper.…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…Frequent unsatisfactory contact with children was observed to double the risk of all-cause dementia although unsatisfactory relationships with children with less frequent contact yielded a cognitive benefit, perhaps by stimulating socio-affective cognitive abilities (Fratiglioni et al, 2000)! Socially engaging leisure, recreational and productive activities gained through social networks, social ties, and social supports that link individuals to others are associated with reduced all-cause dementia risk (Fabrigoule et al, 1995;Wang et al, 2002;Niti et al, 2008). Conversely, reduced social engagement (Bassuk et al, 1999) and loneliness (Wilson et al, 2007) increase the odds of cognitive decline.…”
Section: Social Engagementmentioning
confidence: 99%